2021
DOI: 10.37349/ei.2021.00025
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mucosal immunity and novel prophylactic and therapeutic strategy in combating COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) emerges as an expeditiously growing pandemic, in the human population caused by the highly transmissible RNA virus severe acute respiratory syndrome of coronavirus 2 (SARS-CoV-2). Prognosis of SARS-CoV-2 infection predominantly occurs at the angiotensin-converting enzyme 2 receptor and transmembrane protease serine type 2 positive (ACE2 + TMPRSS2)+ epithelial cells of the mucosal surface like nasal, oral mucosae, and/or the conjunctival surface of the eye where it has intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…The intradermal vaccination led to a high activation of TLR7 in both mice and humans, as well as TLR8 in humans [117]. This immunization also led to the production of type I interferon, as well as pro-inflammatory cytokines and chemokines [118]. In a similar vein, it was shown that RNAdjuvant (CureVac AG), which is an unmodified, single-stranded RNA that is stabilized by a cationic carrier peptide, had adjuvant effect in the context of vaccines that do not include messenger RNA [119].…”
Section: Modulation Of Immunogenicitymentioning
confidence: 99%
“…The intradermal vaccination led to a high activation of TLR7 in both mice and humans, as well as TLR8 in humans [117]. This immunization also led to the production of type I interferon, as well as pro-inflammatory cytokines and chemokines [118]. In a similar vein, it was shown that RNAdjuvant (CureVac AG), which is an unmodified, single-stranded RNA that is stabilized by a cationic carrier peptide, had adjuvant effect in the context of vaccines that do not include messenger RNA [119].…”
Section: Modulation Of Immunogenicitymentioning
confidence: 99%
“…Mucosal tolerance is an active immune response that is regulated by several tissue and cells in our body . MALT is an essential part of mucosal immunity, which is considered primary tissues where inhaled or ingested viruses are lodged. Also, the mouth, pharynx, and esophagus, as well as the gastrointestinal, respiratory, and urogenital systems, are all considered mucosal tissues, which play an important role in mucosal immunity.…”
Section: Mechanism Of Action Of Mucosal Immune Systemmentioning
confidence: 99%
“… Delay in identifying viral pathogens: This delay worsens the patients’ prognosis by leading to critical conditions such as acute respiratory distress syndrome (ARDS) ( Bhatnagar et al, 2021 , Liu et al, 2019 ). Altered production of defensive barriers: Lack of mucins and glycoproteins contributes to an unchallenging entrance of viral pathogens ( Chatterjee et al, 2021 , Xu et al, 2019 ). Intrathymic infiltration of adipose tissue: By affecting the production of T cells and memory lymphocytes, this could result in a compromised function of the adaptive immune system against SARS-CoV-2 ( Ongrádi and Kövesdi, 2010 ).…”
mentioning
confidence: 99%
“…Altered production of defensive barriers: Lack of mucins and glycoproteins contributes to an unchallenging entrance of viral pathogens ( Chatterjee et al, 2021 , Xu et al, 2019 ).…”
mentioning
confidence: 99%